Implementasi Analisis SWOT Dalam Strategi Pemasaran Pada Produk Tabungan Wadiah - Faisal, Ignal; Fasa, Muhammad Iqbal (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
Wadiah savings is one of the savings accounts offered by Bank Syariah Indonesia, with the aim of allowing customers to save money and make transactions easily and cheaply. Due to a lack of knowledge about the products at Bank Syariah Indonesia, some people still think they are the same as conventional banks. Therefore, Bank Syariah Indonesia must apply SWOT analysis in an appropriate marketing strategy to increase the market share of wadiah savings users. This research uses qualitative research, using observation, documentation, literature study and interview techniques. The results of this research show that the opening of wadiah savings increases every day. Sharia banks continue to strive to collaborate with various financial institutions to promote wadi'ah savings.